2016
DOI: 10.1093/annonc/mdw135
|View full text |Cite
|
Sign up to set email alerts
|

A genomic case study of mixed fibrolamellar hepatocellular carcinoma

Abstract: We report the first comprehensive genomic analysis of a case of mixed conventional and fibrolamellar HCC (mFL-HCC). This study confirms the expression of DNAJB1:PRKACA, a fusion previously associated with pure FL-HCC but not conventional HCC, in mFL-HCC. These results indicate the DNAJB1:PRKACA fusion has diagnostic utility for both pure and mixed FL-HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 18 publications
1
10
1
Order By: Relevance
“…All the large and small Dnajb1–Prkaca -elicited lesions showed the cytological characteristics of FL-HCC described above. Only one lesion, in fact, contained premalignant clear cells intermingled with oncocytic hepatocytes with prominent nucleoli and eosinophilic cytoplasm (Supplementary Figure 3 C ), in accordance with the observation that FL-HCC may occasionally appear as a mixed-FL-HCC, which has also been reported positive for the fusion 25 . Genomic DNA analysis of laser capture microdissected small lesions confirmed the presence of the oncogenic Dnajb1–Prkaca aberration (Supplementary Figure 3 D ).…”
Section: Resultssupporting
confidence: 88%
“…All the large and small Dnajb1–Prkaca -elicited lesions showed the cytological characteristics of FL-HCC described above. Only one lesion, in fact, contained premalignant clear cells intermingled with oncocytic hepatocytes with prominent nucleoli and eosinophilic cytoplasm (Supplementary Figure 3 C ), in accordance with the observation that FL-HCC may occasionally appear as a mixed-FL-HCC, which has also been reported positive for the fusion 25 . Genomic DNA analysis of laser capture microdissected small lesions confirmed the presence of the oncogenic Dnajb1–Prkaca aberration (Supplementary Figure 3 D ).…”
Section: Resultssupporting
confidence: 88%
“…liver cancer is usually occult in onset and no effective screening measure is able to screen for the disease validly and reliably; therefore, two-thirds of cases are not diagnosed until an advanced stage (10,11). furthermore, liver cancer is often resistant to chemotherapeutic drugs because it usually originates from pre-existing liver diseases (12,13). these factors largely contribute to the high mortality rate of liver cancer.…”
Section: Microrna-493-5p Promotes Apoptosis and Suppresses Proliferatmentioning
confidence: 99%
“…Recent studies have characterized at molecular level a variant of FL-HCC, known as mixed fibrolamellar hepatocellular carcinoma (Mix-FL-HCC) and characterized by the presence of both pure FL-HCC and conventional HCC component within the same tumors [ 53 ]. In these rare tumors, the DNAJB1-PRKACA fusion transcript is expressed at high levels [ 53 ].…”
Section: Genetic Abnormalities In Liver Cancermentioning
confidence: 99%
“…Recent studies have characterized at molecular level a variant of FL-HCC, known as mixed fibrolamellar hepatocellular carcinoma (Mix-FL-HCC) and characterized by the presence of both pure FL-HCC and conventional HCC component within the same tumors [ 53 ]. In these rare tumors, the DNAJB1-PRKACA fusion transcript is expressed at high levels [ 53 ]. Importantly, the analysis of RNA-sequencing data from The Cancer Genome Atlas (TCGA) for more than 9000 tumors across about 30 cancer types showed that the DNAJB1-PRKACA fusion is specific for FLHCCs [ 54 ].…”
Section: Genetic Abnormalities In Liver Cancermentioning
confidence: 99%